Neurologic Manifestations of Germline GATA2 Deficiency: A Report of Two Cases - Alastair K. Williams; Ryan J. Stubbins; Eric McGinnis; John A. Maguire; Persia Pourshahnazari; Claudie Roy; Luke Y.C. Chen; Thomas J. Nevill (Annals of Internal Medicine: Clinical Cases)
Germline pathogenic mutations in the GATA2 gene, a critical transcription factor in hematopoietic and neurologic development, are known to cause various syndromes characterized by both hematopoietic (for example, monocytopenia, myelodysplastic syndrome) and extra-hematopoietic (for example, lymphedema, atypical and mycobacterial infections) manifestations. Neurologic features of this disease need to be better understood. We describe 2 patients with germline GATA2 deficiency who developed a progressive neurologic illness characterized by upper motor neuron weakness, bulbar and cerebellar dysfunction, pronounced white matter magnetic resonance imaging abnormalities, and noninfectious leukoencephalopathy with cerebellar degeneration. These neurologic findings may be a novel extra-hematopoietic manifestation of germline GATA2 deficiency.